Self-Compassion Increases Life Satisfaction in Singles Who Want to Get Married: [Welas Asih Diri Meningkatkan Kepuasan Hidup Pada Lajang Ingin Menikah] - Maryanto, Gracetia Ratna Honesty; Himawan, Karel Karsten; Akhtar, Hanif (Faculty of Psychology, Universitas Surabaya, 2024)
For most societies with strong patriarchal values, marriage is part of cultural expectations, causing challenges and social stress for single individuals of marriageable age. This phenomenon can also be observed in people in Central Java. In an effort to increase the life satisfaction of single individuals amidst high cultural expectations, this quantitative study aims to explore the influence of self-compassion on life satisfaction. A cross-sectional survey was conducted on 138 single individuals aged between 25-35 years (Mage = 27.84; SD = 3.014). Regression analysis was utilized to determine the contribution of self-compassion to life satisfaction. The results show that self-compassion influences the life satisfaction of single women (r = .537; p = .000) and men (r = .270; p = .34) in Central Java. This means that self-compassion as a psychological strategy can help singles to experience life satisfaction even though they experience social pressure regarding their single status. Bagi kebanyakan masyarakat dengan nilai patriarkal yang kuat, pernikahan merupakan bagian dari ekspektasi budaya, menyebabkan tantangan dan tekanan sosial bagi individu lajang berusia siap menikah. Fenomena ini juga dapat diobservasi pada masyarakat di Jawa Tengah. Sebagai upaya untuk meningkatkan kepuasan hidup individu lajang di tengah ekspektasi budaya yang tinggi, studi kuantitatif ini bertujuan untuk mengeksplorasi pengaruh welas asih diri terhadap kepuasan hidup. Survei cross-sectional dilakukan terhadap 138 individu lajang berusia antara 25-35 tahun (Musia = 27,84; SD = 3,014). Analisis regresi digunakan untuk mengetahui kontribusi welas asih diri terhadap kepuasan hidup. Hasil menunjukkan bahwa welas asih diri berpengaruh pada kepuasan hidup perempuan (r = 0,537; p = 0,000) dan laki-laki (r = 0,270; p = 0,34) lajang di Jawa Tengah. Hal ini berarti welas asih diri sebagai strategi psikologis dapat membantu lajang tetap mengalami kepuasan hidup walaupun mengalami tekanan sosial mengenai status lajangnya.